Cerebral venous sinus stenting and jugular bulb embolization for pulsatile tinnitus: A case report - Xu, Mengjiao; Dong, Xiaobo; Zheng, Can; Zheng, Tao; Wang, Gesheng (Frontiers in Neurology, 2024)
Background Pulsatile tinnitus (PT) is a rare form of tinnitus that aligns with the heartbeat. It is typically brought on by lesions with significant vascularity, which produce aberrant sound conduction and increase the risk of mental health issues and hearing loss. Venous PT is more prevalent than arterial PT. Open procedures or interventional procedures can be used to treat PT. We present here a case of PT caused by venous luminal stenosis combined with jugular bulb (JB) malformation, which was improved by stenting and JB embolization. Case presentation A 59-year-old woman presented with long-term tinnitus consistent with heart rhythm and hearing loss, accompanied by anxiety, insomnia, and depression. The results of brain MRV, CT, and DSA showed stenosis of the right sigmoid sinus and high jugular bulb (JB) with dehiscence of the JB wall. The patient saw a significant improvement in PT symptoms following sigmoid sinus stenting and spring coil embolization of the high JB, following the diagnosis of PT. The patient had no PT recurrence for the course of the 31-month follow-up period. Conclusion In the present PT case, there was a simultaneous onset of the right sigmoid sinus stenosis and the high JB with the JB wall abnormalities. Sigmoid sinus stenting and spring coil embolization of high JB may be a treatment for the PT, but the prevention of post-stenting complications is still an issue that requires great attention and needs further study.